Investigation of the effect of the water to powder ratio on hydraulic cement properties. Issue 8 (August 2019) - Koutroulis, A.; Batchelor, H.; Kuehne, S.A.; Cooper, P.R.; Camilleri, J.
Abstract: Objective: The use of rheological properties to determine the optimal water: powder ratio of tricalcium silicate-based prototype materials incorporating alternative radiopacifiers and fillers. Determination of how the proportion of water incorporated affected the physicochemical behaviour of the materials. Methods: Endodontic cements replaced with 30% radiopacifier, and additions of calcium phosphate and micro-silica were tested. The unmodified cements were mixed with a 0.35 water: powder ratio which served as control. At this water: powder ratio, unmodified Portland cement without any addition had an adequate consistency and furthermore it has been well characterized. Assessment of material rheological properties enabled adjustment of the water: powder ratio in each material to provide comparable viscosity values to those of the pure cement. The flowability, phase analysis and calcium release were measured for both viscosity-matched and the standard 0.35 water: powder ratio blends. The prototype materials with the adjusted water: powder ratios were also characterized by scanning electron microscopy, energy-dispersive spectroscopy and evaluated for radio-opacity. Results: The use of the 0.35 water: powder ratio is not appropriate when changing the radiopacifier and incorporating additives. Zirconium oxide did not vary the water: powder ratio but tantalum oxide and calcium tungstate resulted in an increase and decrease in water demand respectively. Using the standard 0.35 ratio when the mixture had a low water demand resulted in higher flowability values and calcium release in solution. Micro-silica and calcium phosphate altered the hydration of the materials. All materials were adequately radiopaque. Significance: Rheological assessment is an easy reproducible way to determine the water: powder ratios of materials with varying amounts of additives and radiopacifiers during development. Modifications to the water: powder ratio affects material properties.